Determinants of Whistleblowing Intention of Employees in Universities: Evidence from Indonesia - Pratolo, Suryo; Sadjiman, Vidya Putri; Sofyani, Hafiez (Universitas Muhammadiyah Surakarta, 2020)
Corruption in higher education institutions (HEI) is serious issue that has become a focus by many parties. The amount of state losses caused by fraudulent behavior in the management of university finances makes research related to whistleblowing at universities very urgent. Hence, this study aims to examine how perceived personal costs, perceived fraud seriousness, and attitude influence whistleblowing intention of university employees. This research was conducted in two universities in Manado, North Sulawesi, Indonesia. The research samples were permanent employees including lecturers and staffs. Data obtained by distributing questionnaires directly to the respondents. Hypothesis testing uses multiple regression analysis techniques. This study found that perceived personal costs have a negative effect on whistleblowing intention. Meanwhile, perceived fraud seriousness and attitude have a positive effect on whistleblowing intention. Discussion, implications and further research suggestions are presented in this paper